A Blended Cognitive–Behavioral Intervention for the Treatment of Postpartum Depression: A Case Study. (October 2022) - Branquinho, Mariana; Canavarro, Maria Cristina; Fonseca, Ana
Postpartum depression is a highly prevalent mental health problem with harmful consequences for women, babies, and mother–infant relationships. Cognitive–behavioral therapy (CBT) is among the most effective treatment options for postpartum depression. However, a large number of postpartum women do not seek professional help, suggesting the need for new treatment delivery formats. The present article describes the application of Be a Mom Coping with Depression, a blended CBT treatment for postpartum depression, for a 31-year-old postpartum woman. The intervention was provided over a period of 13 weeks, integrating seven biweekly sessions with a psychologist and six sessions within an online program, and it is described in detail. A summary of the patient's progress and the results obtained throughout treatment is reported. At the end of the intervention, a significant decrease in depressive and anxiety symptoms was observed, as well as increased perceived maternal self-efficacy, higher psychological flexibility, and higher self-compassion. This case study provides encouraging data for the preliminary evidence of the acceptability, feasibility, and efficacy of the Be a Mom Coping with Depression intervention in the reduction of depressive symptoms during the postpartum period. Advantages of this treatment format and implications for clinical practice and future research are discussed.